One lens three views - Maytham-Bailey, Sandra (Centre for Film and Media Studies, 2014)
This document explores the complexity of the Zulu Reed Dance in the context of creating a photographic record of the event in various narrative styles within the genre of documentary photography. The authorphotographer acknowledges their subjective contribution in the image making process, and uses this understanding to demonstrate a continuum of subjectivity that operates depending on the visual narrative being constructed. To contextualise the photographers approach, the document explores the social, political and economic landscape, and the dominant visual record produced by media. A qualitative review of six national newspapers demonstrates that the media view is relatively generic and does not attempt to engage with alternative perspectives. The document also explores critical theory on the subject of the qualification of a photographer to provide an accurate record outside of their cultural status. The author considers the validity of image production and the reception of the work as indicative of a continuum of subjectivity. To demonstrate this fluidity, the photographer produces three photo essays, all made at the same event at the same time with very different narrative outcomes. These photo essays can be found the accompanying book titled 'One lens three views'.